Motivasi Rasulullah Menghadapi Tahun Kesedihan dalam Kerangka Self-Determination Theory - Ariansyah, Ilham Yosi (INTELEKSIA: Jurnal Pengembangan Ilmu Dakwah, 2023)
MOTIVATION OF RASULULLAH TO FACE THE YEAR OF GRIEF FROM A STANDPOINT OF SELF-DETERMINATION THEORY. Motivation plays an important role in determining the success of a preacher's da'wah. The reality of the motivation within the dai can be observed in the efforts of the Prophet when he faced the year of sadness. A description of the motivation of the Prophet in facing the year of sadness was carried out in the framework of self-determination theory (SDT). The SDT framework was chosen because it was able to describe the types, characteristics, and aspects that formed the motivation of the Prophet in the event. Descriptive qualitative methodology was used in this study. Historical library data is used as a data source. The results of the historical literature explain that the Prophet had motivations: (1) belief in the greatness of Allah, the truth of Islam and the truth of Allah's promise of reward in the hereafter (2) solely to carry out God's command to preach so that more people would know and believe in the teachings of Islam, and (3) solve various actual problems that hinder the smooth running of da'wah activities. This motivation is a type of autonomous motivation sub internalized extrinsic motivation, with the characteristics of a personal appreciation of the important values ​​of the various efforts carried out, having independent considerations to do or not do activities, and there is coherence with previously owned values. Internalized extrinsic motivation in the Prophet was formed because of the fulfillment of three aspects of basic needs in SDT, namely competence, autonomy, and relatedness as well as the existence of controlled motivation that is integrated to fulfill these needs.